Understanding the Chemistry of Disinfection By-Products in Swimming Pools to Minimise Chemical Health Risks - Carter, Rhys Aaron Ainsley (Curtin University, 2019)
Swimming pools contain organic compounds originating from both filling water and bather load. These organic compounds react with added disinfectants to form unwanted disinfection by-products in the pools. This Thesis presents an improved understanding of the occurrence and formation of disinfection by-products in pools and their potential chemical health risks. It provides significant knowledge for pool operators and the leisure industry to drive improvements in the chemical water quality of pools in the future.